Environmental variation structures northern peatland soil microbiome composition and function in a reindeer herding area exclosure experiment - Välikangas, Tommi; Fritze, Hannu; Pitkänen, Juha-Matti; Peltoniemi, Krista; Järvi-Laturi, Eeva; Christensen, Torben R; Väisänen, Maria; Lämsä, Juho; Paavola, Riku; Hultman, Jenni (Oxford University Press, 2026)
Northern peatlands store large carbon stocks but are sensitive to disturbance. Hydrology, vegetation, herbivory and snow conditions may affect soil microorganisms involved in methane (CH4) cycling and nitrous oxide (N2O) production/reduction. We investigated how reindeer exclusion and snow depth (increased and reduced relative to ambient) manipulations (ongoing for three seasons) influenced archaeal and bacterial communities in a boreal rich fen. Metagenomic (MG) and metatranscriptomic (MT) sequencing were combined with pore-water chemistry and CH4 flux measurements to link the microbiome to ecosystem processes. Microbial communities differed between outside and inside the exclosure. However, these patterns primarily reflected underlying hydrological variation. Slightly wetter inside plots showed higher expression of denitrification genes (norB and nosZ) and lower (nirS+nirK)/nosZ ratios, indicating greater potential for complete denitrification to N2 instead of N2O. Methane dynamics were mainly associated with vegetation: plots associated with Carex rostrata exhibited lower pmoA/mcrA ratios and elevated CH4 fluxes. Snow manipulations had subtle effects: reduced snow depth decreased the expression of taxa dependent on microbial interactions, while effect to the investigated metabolic marker genes was small. Overall hydrology, leading to variations in redox conditions and nutrient availability, together with vegetation appeared as the primary drivers on microbial greenhouse gas (GHG) processes in this peatland.
Keywords: hydrology; herbivory; rich fen; carbon cycle; nitrogen cycle